Study on Road Safety Audit of Existing Kanti Rajmarg: A Case Study of (Tika Bhairab- Baguwa Section) of Kanti Rajmarg at Lalitpur, Nepal - Ishar, Neeta Kumary; Dahal, Khet Raj; Tripathi, Ravi Kiran; Parajuli, Ramesh (International Journal on Engineering Technology, 2025)
Ensuring road safety of existing road is crucial to preventing accidents and improving the long-term usability of roadways. This study focuses on a road safety audit (RSA) conducted during the existing phase of the Tika Bhairab-Baguwa section of Kanti Rajmarg in Lalitpur, Nepal. The main aim is to assess the safety performance of the road, identify potential hazards, and highlight design flaws that may lead to accidents in its operation level. Through field observations, surveys, and interviews with road users and experts, the research identified several key safety concerns. These include poor road alignment, narrow lanes, limited visibility, and insufficient signage or markings. Additionally, gaps in traffic law enforcement, coupled with inadequate training for traffic police, contribute to heightened road safety risks. Key findings highlight critical safety concerns such as poor visibility at curves, inadequate pedestrian crossings, lack of proper signage, and hazardous roadside encroachments. Based on questionnaire survey major problems associated with road safety of Kanti Rajmarga with highest RII value were narrow lane width, poor road signage and marking both with RII value 0.85. Similarly, poor road signage and marking, improper alignment both with RII value 0.8. The main cause of narrow lane width was found due to budget constraint, poor plaining and hilly terrain. Based on the results, practical recommendations are proposed, including improved road markings, installation of guardrails, enhanced street lighting, and better traffic management at conflict zones, increasing law enforcement efforts, and providing better training for traffic police and drivers are critical steps to making the road safer. A good drainage system should be created to prevent flooding and erosion, and strong barriers should be placed near steep drops. These recommendations aim to reduce risks and ensure the safety of all road users. Thus this study contributes to the broader discourse on road safety in Nepal by providing a case-specific assessment and actionable solutions. The findings can aid local authorities in implementing effective safety upgrades, ultimately reducing accidents and ensuring safer mobility on Kanti Rajmarg.